(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Background: Genetic susceptibility is a factor in the development of ophthalmic complications in type 2 diabetes mellitus (T2DM). There are differences between polymorphisms of toll-like receptor-4 (TLR4) in terms of their association with microvascular complications of T2DM. Purpose: To assess the association of TLR4 rs1927911 polymorphism with diabetic retinopathy (DR) and diabetic macular edema (DME) in T2DM. Material and Methods: This study involved 81 type 2 diabetics (81 eyes) with both DR and DME and 50 type 2 diabetic controls (50 eyes) having normalized carbohydrate metabolism and neither DR nor DME. TLR4 rs1927911 genotypes were investigated by real time polymerase chain reaction (PCR) using Gene Amp® 7500 PCR System (Applied Biosystems, Foster City, CA) and TaqMan Mutation Detection Assays (Life Technologies, Carlsbad, CA). Results: TLR4 rs1927911 polymorphism was associated with DR and DME (р = 0.021), and the risk of these complications was lower (OR = 0.42; 95% CI, 0.23–0.77) in allele A carriers than in ancestral allele G carriers. rs1927911 genotype distribution was significant by Pearson chi-square test under a dominant model (GG versus GA+AA; χ2 = 6.38; р = 0.012; OR = 0.37; 95% CI, 0.18-0.76). After patients were stratified by the stage of DR and the severity of DME, significant differences with regard to genotypes were observed only in proliferative DR and severe DME. Carriers of the heterozygous genotype and minor genotype AA showed less severe glycemia, lower HbA1c, and smaller central retinal thickness and total retinal volume than carriers of the ancestral genotype GG; this corresponded to less severe carbohydrate metabolism abnormalities and less severe retinal damage. Conclusion: Pro-inflammatory pathways involve TLR4 under hyperglycemic conditions. Given the role of TLR4 in the mechanisms triggering the immune response, it may be supposed that the activity of these pathways is reduced in carriers of rs1927911 polymorphism, and it is this that causes reduced diabetic retinal damage.